Architecture and Landscape in the contemporary City - Adriana Sarro (Agathón)
In the last years, the Italian landscape has been constantly degraded with buildings that do not always have the sense of belonging to the context, landscape and history of the places. The article examines some project proposals of the European sphere with critical reflections about the relationship between landscape and contemporary architecture.